2016
DOI: 10.1007/s00268-015-3361-5
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Hospital Discharge Venous Thromboembolism in Colorectal Surgery

Abstract: Background There are limited data regarding the criteria for prophylactic treatment of venous thromboembolism (VTE) after hospital discharge. We sought to identify risk factors of post-hospital discharge VTE events following colorectal surgery.Methods The NSQIP database was utilized to examine patients developed VTE after hospital discharge following colorectal surgery during [2005][2006][2007][2008][2009][2010][2011][2012][2013]. Multivariate analysis using logistic regression was performed to quantify risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…This is also supported by another study showing an excess risk of venous thromboembolism in those undergoing emergency surgery . The size of the risk of thromboembolism we found is consistent with other patients after major surgery, suggesting similar post‐operative risks in inflammatory bowel disease patients and in patients undergoing surgery for colorectal cancer …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is also supported by another study showing an excess risk of venous thromboembolism in those undergoing emergency surgery . The size of the risk of thromboembolism we found is consistent with other patients after major surgery, suggesting similar post‐operative risks in inflammatory bowel disease patients and in patients undergoing surgery for colorectal cancer …”
Section: Discussionsupporting
confidence: 90%
“…36 The size of the risk of thromboembolism we found is consistent with other patients after major surgery, suggesting similar post-operative risks in inflammatory bowel disease patients and in patients undergoing surgery for colorectal cancer. [36][37][38]…”
Section: Prophylaxis Against Venous Thromboembolismmentioning
confidence: 99%
“…Postoperative venous thromboembolism (VTE) is one of the most common post-surgical complications, which may have disastrous impacts on surgical outcomes. 1 VTE includes deep vein thrombosis (DVT) and pulmonary embolism (PE) and is one of the leading causes of morbidity and prolonged hospitalization in surgical patients, 2,3 and it has been accounted for 5e10% of all inhospital deaths in US. 4,5 Although, several VTE preventative guidelines and recommendation have been issued from different surgical societies, 6,7 recent publications demonstrated that there is an incremental trend for VTE occurrences.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the burden of postdischarge VTE has been documented in subsets of patients undergoing resection for abdominal and pelvic malignant diseases, in which the use of extended VTE prophylaxis is founded on strong evidence [6,[18][19][20][21]. However, few studies have examined the association of these risk factors and the development of VTE in thoracic surgical patients.…”
mentioning
confidence: 99%